Navigating Transnational Challenges: The Influence of Social Media on Indonesian Student Migrants in Sweden During the COVID-19 Era - Hidayati, Inayah (Universitas Andalas, 2024)
This study examines how social media has impacted the decision-making process of Indonesian students in Sweden who are considering migration during the COVID-19 pandemic. Given the unique circumstances of the pandemic, health and safety have become critical factors in the decision-making processThe research was conducted using quantitative and qualitative methods, which were highly effective in gathering data. A survey was conducted with 33 participants, who were selected using accidental sampling. In addition, open interviews were conducted with 10 participants from different countries, which provided valuable insights into the subject matter. Data was collected through online questionnaires and interviews across multiple social media platforms. Although there were some potential limitations in data quality and participant engagement, the methods utilized in this study were highly effective and produced reliable results. The study found that social media was vital in helping Indonesian students make informed migration decisions and obtain information about the pandemic. In particular, social media facilitates knowledge sharing and communication with friends and colleagues. However, the pandemic created temporary obstacles for migrants considering returning to Indonesia due to safety and health concerns.